Economic reconstruction in Pakistan : problems, policies and prospects - Ahmad, Rafiq; Naseem, S. M.; Ghouse, Agha Mohamed (Karachi : Pakistan Economic Association, 1973)
This volume examines problems, policies and prospects of economic reconstruction in Pakistan based on papers presented to the 16th annual All Pakistan Economic Conference, Islamabad University, Islamabad, Feb. 18-20, 1973 / editors Rafiq Ahmad, S. M. Naseem, Agha M. Ghouse.
Includes bibliographical references.
lje 04/10/2018
Loans
Keywords: Economic development; Pakistan